Chemoradiotherapy Versus Chemotherapy Alone for Advanced Esophageal Squamous Cell Carcinoma: The Role of Definitive Radiotherapy for Primary Tumor in the Metastatic Setting - Li, Li-Qing; Fu, Qing-Guo; Zhao, Wei-Dong; Wang, Yu-Dan; Meng, Wan-Wan; Su, Ting-Shi (Frontiers in Oncology, 2022)
Introduction: The role of definitive radiotherapy in advanced esophageal squamous cell carcinoma (ESCC), especially in metastatic setting, remains unclear. We aimed to investigate the efficacy and of chemoradiotherapy versus chemotherapy alone in these selected patients. Methods: We retrospectively evaluated 194 newly diagnosed patients with advanced ESCC, including 97 cases with locally advanced and 97 cases with distant metastatic disease, who underwent definitive chemoradiotherapy (CRT) or chemotherapy (CT) alone. The cumulative overall survival (OS) and progression-free survival (PFS) were evaluated with log-rank test. Propensity score matching was used to control to simulate random allocation. Subgroup analysis was performed in the locally advanced disease and metastatic disease. Results: After matching, 63 well-paired patients were selected. The adjusted median OS (12.5 vs. 7.6 months, P= 0.002) and PFS (9.0 vs. 4.8 months, P= 0.0025) in the CRT group were superior to that in the CT alone group. Further subgroup analysis revealed that CRT conferred survival benefit to both locally advanced and metastatic cohort. For patients with distant metastasis, median OS (12.9 vs. 9.3 months, P= 0.029) and PFS (9.9 vs. 4.0 months, P=0.032) in the CRT group were superior to that in the CT group. In multivariate Cox regression analysis of the entire cohort, additional definitive radiotherapy was independently associated with better PFS (P=0.001) and OS (P=0.041). Conclusions: In both locally advanced and metastatic ESCC, additional definitive dose radiotherapy was associated with improved clinical outcomes. More consideration should be given to its application in the metastatic setting.